Zero-Inflated NGINAR(1) process. Issue 3 (1st February 2019) - Ristić, Miroslav M.; Bourguignon, Marcelo; Nastić, Aleksandar S.
ABSTRACT: In this paper, we develop a zero-inflated NGINAR(1) process as an alternative to the NGINAR(1) process (Ristić, Nastić, and Bakouch2009 ) when the number of zeros in the data is larger than the expected number of zeros by the geometric process. The proposed process has zero-inflated geometric marginals and contains the NGINAR(1) process as a particular case. In addition, various properties of the new process are derived such as conditional distribution and autocorrelation structure. Yule-Walker, probability based Yule-Walker, conditional least squares and conditional maximum likelihood estimators of the model parameters are derived. An extensive Monte Carlo experiment is conducted to evaluate the performances of these estimators in finite samples. Forecasting performances of the model are discussed. Application to a real data set shows the flexibility and potentiality of the new model.